1938
DOI: 10.1113/jphysiol.1938.sp003671
|View full text |Cite
|
Sign up to set email alerts
|

The rate of adaptation of cutaneous nerve endings in the frog

Abstract: STUDIES of the action potentials in sensory nerve fibres have led to a grouping of sensory endings as slowly adapting and rapidly adapting, the former giving a long-continued and the latter a brief discharge to a persistent stimulus. Many of the receptors in the frog's skin are of the rapidly adapting type, the discharge to a continuous stimulus lasting less than 0-1 sec.; others adapt somewhat more slowly (the discharge lasting from 1 to 100 sec.), while the stretch receptors in mammalian muscle, lung and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1940
1940
1963
1963

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Thus Matthews [1931] has shown that reduction of Ca++ leads to a spontaneous discharge of the stretch receptors in frog muscle, and Talaat [1933] has found the same result with endings in frog skin, whilst recently Dun & Finley [1938] have produced very rapid adaptation in the tactile endings of the frog by increasing the Ca++. An increase of K+ depresses and may abolish the response of these endings.…”
Section: Part IImentioning
confidence: 87%
See 1 more Smart Citation
“…Thus Matthews [1931] has shown that reduction of Ca++ leads to a spontaneous discharge of the stretch receptors in frog muscle, and Talaat [1933] has found the same result with endings in frog skin, whilst recently Dun & Finley [1938] have produced very rapid adaptation in the tactile endings of the frog by increasing the Ca++. An increase of K+ depresses and may abolish the response of these endings.…”
Section: Part IImentioning
confidence: 87%
“…The nerve endings stimulated by hair movement can therefore be described as rapidly adapting, although the short duration of the discharges might be due to mechanical factors, such as the yielding oftissues, rather than to the intrinsic properties of the endings [cf. Dun & Finley, 1938]. But the investigations referred to have been concerned with the covering hairs of the body and limbs; the large vibrissae or tactile hairs of the face have not been specially examined.…”
mentioning
confidence: 99%
“…However, it seems that in the classifications of other authors the term 'adaptation' merely refers to the duration of a discharge burst while frequency decay has been disregarded. Moreover, with the exception of DUN & FINLEY (1938), the duration of discharges has been only described as 'short' or 'long' and/or 'phasic' or 'tonic' . In this study the rapidly and the slowly adapting units are classified taking into account both of the duration of discharges (more or less than 1 sec.)…”
Section: Discussionmentioning
confidence: 99%